Grasshoppers of the Mascarene Islands: new species and new records (Orthoptera, Caelifera) - Hugel, Sylvain (Zootaxa, 2014)
The grasshopper fauna of Mascarene Islands (Mauritius, Rodrigues and La Réunion), in South Western Indian ocean is examined. Numerous field surveys and examination of museum specimens recorded twenty species of Grasshoppers on the archipelago. Five of them are new records, including a new species: Odontomelus ancestrus n. sp. restricted to Round Island, a 2 km² islet North to Mauritius. Despite intensive searching, five of the non endemic species once recorded on the archipelago have not been recorded again and might correspond to temporary settlements/introductions. A key to Mascarene grasshoppers is given.